4(2x + 3) = 2(3x - 4)


one solution
infinite solutions * my answer*
no solution

6 - a = 1/3(9a - 18)
one solution * my answer*
infinite solutions
no solution

3(4x - 3) - 7x = 5x - 9
one solution
infinite solutions *my answer*
no solution

4(2x - 3) - 4x (answer all that apply)

4x – 12 *my answer*
3x – 4

3(2x – 6) *my answer*

4(x – 5)

2 answers

4(2x + 3) = 2(3x - 4)
8x+12 = 6x-8
2x = -20
x = -10
Bzzzt

6 - a = 1/3(9a - 18)
18-3a = 9a-18
12a = 36
a = 3
correct

3(4x - 3) - 7x = 5x - 9
12x-9-7x = 5x-9
5x-9 = 5x-9
correct - the same line

4(2x - 3) - 4x
8x-12-4x
4x-12
2(2x-6)
4(x-3)
only your first choice is correct
Is it correct